Papua New Guinea : 2012 Article IV Consultation: Staff Report; Public Information Notice. (IMF Staff Country Reports; Country Report ;, 2012)
Papua New Guinea has seen solid economic growth over the past decade, supported by sound macroeconomic policies. This 2012 Article IV Consultation discusses that the financial sector in Papua New Guinea remains profitable and well capitalized, but vulnerabilities have increased. Executive Directors have commended the authorities for achieving macroeconomic stability and a sustainable fiscal position. To preserve these achievements and promote inclusive development, it will be important to combine steady, affordable growth in government spending with improvements in public financial management and expenditure effectiveness.